Biological significance of complex N-glycans in plants and their impact on plant physiology - Strasser, Richard (Frontiers in Plant Science, 2014)
Asparagine (N)-linked protein glycosylation is a ubiquitous co- and post-translational modification which can alter the biological function of proteins and consequently affects the development, growth and physiology of organisms. Despite an increasing knowledge of N-glycan biosynthesis and processing, we still understand very little about the biological function of individual N-glycan structures in plants. In particular, the N-glycan processing steps mediated by Golgi-resident enzymes create a structurally diverse set of protein-linked carbohydrate structures. Some of these complex N-glycan modifications like the presence of beta1,2-xylose, core alpha1,3-fucose or the Lewis a-epitope are characteristic for plants and are evolutionary highly conserved. In mammals, complex N-glycans are involved in different cellular processes including molecular recognition and signalling events. By contrast, the complex N-glycan function is still largely unknown in plants. Here, in this short review I focus on important recent developments and discuss their implications for future research in plant glycobiology and plant biotechnology.